A multi-methodological approach for assessing sustainability of urban projects. Issue 1 (12th January 2015) - Bottero, Marta
Abstract : Purpose: – The purpose of this paper is to propose a multi-methodological approach for assessing the sustainability of urban projects. The proposed framework has the objective of addressing the different dimensions involved in the analysis (economic, environmental, social, technological, cultural, etc.), following the subsequent phases for the definition of the projects (from a very general masterplan to more detailed preliminary projects). Design/methodology/approach: – The multi-methodological approach is organized according to subsequent steps, involving the application of different evaluation methods, namely SWOT analysis, multicriteria analysis, discounted cash flow analysis and sensitivity analysis. With the aim of better illustrating the proposed approach, the method is applied on a real case concerning the project of a new boulevard in the city of Skopje. Findings: – The proposed approach resulted to be successful in structuring the complex planning context and in increasing and improving the information for the project, thus acting as a learning process. Originality/value: – The paper is based on the experimentation of an hybrid approach for addressing planning process. The multi-methodological framework can be useful in supporting decision making process in the domain of urban projects. In this sense, the proposed framework is able to communicate the planners', designers' and decision maker's perspectives, to enhance transparency in the decision process and thus to increase acceptance.